2003
DOI: 10.1063/1.1572959
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of resonant Raman scattering in double-wall carbon nanotubes

Abstract: The temperature-dependent frequency shift of resonant Raman spectra of double-wall carbon nanotubes is investigated in the range of 78–650 K. We show here that different radial breathing mode (RBM) peaks, which are relative to different tube diameters, have a different temperature coefficient of frequency shift, and the larger diameter carbon nanotubes have more RBM frequency downshift with increasing temperature. We attribute the RBM frequency variation to the temperature dependence of the stretching force co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
62
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 20 publications
(16 reference statements)
12
62
0
1
Order By: Relevance
“…16-18͒ and for DWCNTs. 19 Osswald et al found this rate for DWCNTs when fitting two bands at −0.026 and −0.028 cm −1 /K. 15 Chiashi et al found the same result for the G + peak of SWCNT at −0.028 cm −1 /K.…”
supporting
confidence: 59%
“…16-18͒ and for DWCNTs. 19 Osswald et al found this rate for DWCNTs when fitting two bands at −0.026 and −0.028 cm −1 /K. 15 Chiashi et al found the same result for the G + peak of SWCNT at −0.028 cm −1 /K.…”
supporting
confidence: 59%
“…49 Theory shows that elliptical deformation is energetically favourable. Flattening of the tubes is a transition observed for a large diameter range 45 and is predicted 50 to vary as 1/d 3 . For DWCNTs 15,16 several calculations have shown a small reinforcement of the tube and a transition to the elliptical shape as is observed for SWCNTs (Table 1).…”
Section: Summary Of Pressure-and Temperature-induced Effects Of the Dmentioning
confidence: 99%
“…Further analysis of the G and 2D modes shows that neither their shapes nor positions are affected by the change in the φ angle for low laser power densities (LPDs). For higher LPD, mode positions begin to shift toward lower frequencies because laser light absorption induces thermal expansion of the sp 2 lattice [11][12][13][14][15][16]. However, these shifts for fixed power densities are φ dependent!…”
mentioning
confidence: 99%